2020
DOI: 10.5055/jom.2020.0548
|View full text |Cite
|
Sign up to set email alerts
|

Staff time requirements for postoperative pain management: Comparison of sufentanil sublingual tablet system and intravenous patient-controlled analgesia

Abstract: Objective: Assessment and allocation of required staff time for postoperative pain management for two different patient-controlled technologies, sufentanil sublingual tablet system (SSTS) and intravenous analgesia (PCiA).Design: Activity-based evaluation.Setting: The study was conducted at four German hospitals based on the availability of the two technologies studied and their respective bed capacity broadly reflecting the German hospital landscape. Patients and participants: Staff activities were recorded fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Even if this difference was not significant, which could be explained by the small sample size, nausea was the main reason for dropping out the study and should be taken into consideration. Although studies showed that SSTS could save time at the ward [17, 26, 29], the most interesting advantage from the use of SSTS based on our study was the patient’s satisfaction rate, as mentioned in other studies [5, 16]. This satisfaction could be explained by the easy use of this new PCA device and the feeling of personalization due to the thumb tag, but a Hawthorne effect is probably involved because of the open blind design and the novelty of the device.…”
Section: Discussionmentioning
confidence: 99%
“…Even if this difference was not significant, which could be explained by the small sample size, nausea was the main reason for dropping out the study and should be taken into consideration. Although studies showed that SSTS could save time at the ward [17, 26, 29], the most interesting advantage from the use of SSTS based on our study was the patient’s satisfaction rate, as mentioned in other studies [5, 16]. This satisfaction could be explained by the easy use of this new PCA device and the feeling of personalization due to the thumb tag, but a Hawthorne effect is probably involved because of the open blind design and the novelty of the device.…”
Section: Discussionmentioning
confidence: 99%
“…PCA therapies are known to require significant staff time with a varying degree depending on the technology involved. It is therefore interesting to note that noninvasive PCA technologies with less staff time requirements lead to a higher staff satisfaction; however, this relationship has not been directly studied [50][51][52][53].…”
Section: Processes: Reliable and Efficient!mentioning
confidence: 99%